2020
DOI: 10.2478/rjim-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular complications of diabetes: a striking link through protein glycation

Abstract: Diabetes mellitus is a predominant cause of mortality and morbidity worldwide. One of its serious health problems is cardiovascular complications. Advanced glycation end products (AGEs) are a group of heterogeneous toxic oxidant compounds that are formed after a nonenzymatic reaction between monosaccharides and free amino groups of proteins, compound lipids, and nucleic acids. AGE interacts with various types of cells through a receptor for AGE (RAGE). The interaction between AGE and RAGE is responsible for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…This may be proceeded by the glycation process of proteins with its outcome as glycation end products, which present oxidative and proinflammatory effect [ 58 ]. Advanced glycation end products formed after a non-enzymatic reaction between monosaccharides and free amino groups of proteins, lipids, and nucleic acids are responsible for a cascade of inflammation, oxidative stress, and disruption of calcium homeostasis [ 59 ]. The second factor affecting free amino groups is platelet count.…”
Section: Discussionmentioning
confidence: 99%
“…This may be proceeded by the glycation process of proteins with its outcome as glycation end products, which present oxidative and proinflammatory effect [ 58 ]. Advanced glycation end products formed after a non-enzymatic reaction between monosaccharides and free amino groups of proteins, lipids, and nucleic acids are responsible for a cascade of inflammation, oxidative stress, and disruption of calcium homeostasis [ 59 ]. The second factor affecting free amino groups is platelet count.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the levels of anti-AGE EL IgG antibodies were significantly higher in the T2D group compared to the control group, while the levels of anti-AGE EL IgM antibodies were similar to those in the controls ( Figure 1 ). The non-enzymatic glycation of vascular EL is a spontaneous process [ 32 ] that leads to the formation of autoantibodies against epitopes of AGE EL [ 29 ], both in normal aging and in diabetes [ 33 ]. The IgM class of autoantibodies predominates in the early stage of the immune response and later undergoes switching to the IgG class, which has the same antigen specificity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have also covered roles for AGEs/RAGE ligands and RAGE in the pathogenesis of diabetic complications [17,97,98]. Targeting RAGE for the prevention/treatment of diabetic complications, as well as other RAGE-related disorders, is the critical requirement for the discovery of RAGE's innate functions.…”
Section: Small Molecules Targeting the Cytoplasmic Domain Of Rage Int...mentioning
confidence: 99%